Newborn Safety in the Hospital Setting Requires Adequate Nurse Staffing. Issue 3 (May 2021) - Simpson, Kathleen Rice
Abstract : In this issue of MCN, we feature two important articles about newborn safety in the hospital. One presents the evidence for sudden unexpected postnatal collapse in hospitals in the United States with suggestions for prevention and the other details a program to identify near-miss events of baby drops or falls and one health care system's strategies to minimize risk. Recommendations from both research teams highlight safe nurse staffing as a critical aspect of newborn safety in the inpatient setting to avoid preventable newborn harm.